Using anaerobic blood cultures for infants younger than 90 days rarely showed anaerobic infections but increased yields of bacterial growth. (27th February 2018) - Gross, Itai; Gordon, Oren; Benenson, Shmuel; Abu Ahmad, Wiessam; Shimonov, Amir; Hashavya, Saar; Eventov‐Friedman, Smadar
Abstract: Aim: The use of anaerobic blood cultures in infants suspected of bacteraemia is controversial. Our children's hospital uses both aerobic and anaerobic media, regardless of the risk of anaerobic infection, and the aim of this study was to re‐evaluate the use of anaerobic cultures in infants. Methods: We collected retrospective data from 2002 to 2016 on all blood cultures taken from infants younger than 90 days in the Hadassah‐Hebrew University Medical Centre, Jerusalem, Israel. The incidence and characteristics of infants with positive anaerobic blood cultures were assessed. Results: During the study period, 51 035 blood cultures were drawn from 44 304 infants. Of these, 1496 (2.9%) were clinically significant positive cultures. Pathogenic obligatory anaerobic bacteraemia was extremely rare, with only 37 positive cultures (0.07%) from all of the cultures drawn. No specific risk factors for obligatory anaerobic bacteraemia could be defined, but as many as 174 (11.6%) clinically significant isolates were only detected in the anaerobic culture bottle. Conclusion: True anaerobic bacteraemia was extremely rare in neonates. Nevertheless, using anaerobic culture media may increase the overall yield of bacterial culture growth by isolating anaerobic‐facultative bacteria. This should be weighed up against increasing the volume of blood used for the aerobic culture.